Exogenous application of salicylic acid improves freezing stress tolerance in alfalfa - Wang, Xia; Miao, Jiamin; Kang, Wenjuan; Shi, Shangli (Frontiers in Plant Science, 2023)
Freezing stress is one of the most detrimental environmental factors that can seriously impact the growth, development, and distribution of alfalfa (Medicago sativa L.). Exogenous salicylic acid (SA) has been revealed as a cost-effective method of improving defense against freezing stress due to its predominant role in biotic and abiotic stress resistance. However, how the molecular mechanisms of SA improve freezing stress resistance in alfalfa is still unclear. Therefore, in this study, we used leaf samples of alfalfa seedlings pretreatment with 200 μM and 0 μM SA, which were exposed to freezing stress (-10°C) for 0, 0.5, 1, and 2h and allowed to recover at normal temperature in a growth chamber for 2 days, after which we detect the changes in the phenotypical, physiological, hormone content, and performed a transcriptome analysis to explain SA influence alfalfa in freezing stress. The results demonstrated that exogenous SA could improve the accumulation of free SA in alfalfa leaves primarily through the phenylalanine ammonia-lyase pathway. Moreover, the results of transcriptome analysis revealed that the mitogen-activated protein kinase (MAPK) signaling pathway-plant play a critical role in SA alleviating freezing stress. In addition, the weighted gene co-expression network analysis (WGCNA) found that MPK3, MPK9, WRKY22 (downstream target gene of MPK3), and TGACG-binding factor 1 (TGA1) are candidate hub genes involved in freezing stress defense, all of which are involved in the SA signaling pathway. Therefore, we conclude that SA could possibly induce MPK3 to regulate WRKY22 to participate in freezing stress to induced gene expression related to SA signaling pathway (NPR1-dependent pathway and NPR1-independent pathway), including the genes of non-expresser of pathogenesis-related gene 1 (NPR1), TGA1, pathogenesis-related 1 (PR1), superoxide dismutase (SOD), peroxidase (POD), ascorbate peroxidase (APX), glutathione-S-transferase (GST), and heat shock protein (HSP). This enhanced the production of antioxidant enzymes such as SOD, POD, and APX, which increases the freezing stress tolerance of alfalfa plants.